Identification of a cytoplasmic signal for apical transcytosis - Luton, Frédéric (2009)
Polarized epithelial cells contain apical and basolateral surfaces with distinct protein compositions. To establish and maintain this asymmetry, newly made plasma membrane proteins are sorted in the trans-Golgi network for delivery to apical or basolateral surfaces. Signals for basolateral sorting are generally located in the cytoplasmic domain of the protein, while signals for apical sorting can be in any part of the protein and can depend on N-linked glycosylation of the protein. Signals for constitutive transcytosis to the apical surface have not been reported. Here we utilized the polymeric immunoglobulin receptor (pIgR), which is biosynthetically delivered to the basolateral surface. There the pIgR can bind a ligand and, with or without bound ligand, the pIgR can then be transcytosed to the apical surface. We found that the glycosylation of the pIgR did not affect the biosynthetic transport of the pIgR. However, glycosylation had an effect on pIgR apical transcytosis. Importantly, analysis of the cytoplasmic tail of the pIgR suggested that a short peptide segment was sufficient to transcytose the pIgR or a neutral reporter from the basolateral to the apical surface. This apical transcytosis sorting signal was not involved in polarized biosynthetic traffic of the pIgR.